Rethinking Ancient Egypt : Studies in Honor of Ann Macy Roth - Babcock, Jennifer Miyuki; Haney, Lisa Saladino; Prakash, Tara (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Throughout her career, Ann Macy Roth has regularly returned to well-known ancient Egyptian material and visual culture and shed new light on it by employing different approaches and methodologies. In this way, her research has led to new interpretations and readings of ancient Egyptian beliefs and practices while illustrating the importance of and need for continual questioning and re-examination within Egyptology. This volume brings together papers from around the world that follow her tradition of rethinking, reassessing, and innovating. It is intended to honour Roth's significant career as a scholar, mentor, and teacher and to celebrate and continue her dedication to analyzing ancient Egypt from novel perspectives.